A Cost-Benefit and Accurate Method for Assessing Microalbuminuria: Single versus Frequent Urine Analysis. (25th December 2013) - Hemmati, Roholla; Gharipour, Mojgan; Khosravi, Alireza; Jozan, Mahnaz
Abstract : Background . The purpose of this study was to answer the question whether a single testing for microalbuminuria results in a reliable conclusion leading costs saving. Methods . This current cross-sectional study included a total of 126 consecutive persons. Microalbuminuria was assessed by collection of two fasting random urine specimens on arrival to the clinic as well as one week later in the morning. Results . In overall, 17 out of 126 participants suffered from microalbuminuria that, among them, 12 subjects were also diagnosed as microalbuminuria once assessing this factor with a sensitivity of 70.6%, a specificity of 100%, a PPV of 100%, a NPV of 95.6%, and an accuracy of 96.0%. The measured sensitivity, specificity, PVV, NPV, and accuracy in hypertensive patients were 73.3%, 100%, 100%, 94.8%, and 95.5%, respectively. Also, these rates in nonhypertensive groups were 50.0%, 100%, 100%, 97.3%, and 97.4%, respectively. According to the ROC curve analysis, a single measurement of UACR had a high value for discriminating defected from normal renal function state (c = 0.989 ). Urinary albumin concentration in a single measurement had also high discriminative value for diagnosis of damaged kidney (c = 0.995 ). Conclusion . The single testing of both UACR and urine albumin level rather frequent testing leads to high diagnostic sensitivity, specificity, and accuracy as well as high predictive values in total population and also in hypertensive subgroups.